Penerapan Psikologi Behavioristik Untuk Membentuk Disiplin Belajar Di Lingkungan Kelas - Pernandes, Rapi (An-Nuha, 2025)
This study aims to determine the application of behaviorist psychology to form learning discipline in the classroom environment. The study used a qualitative method with a descriptive approach. The focus of the study was to identify the strategies used by teachers and how these strategies affect student behavior. Data collection techniques used were interviews, observations and documentation. Data were analyzed using a thematic approach, which involved coding data to identify key themes related to the application of behaviorist psychology. Data validity was maintained through triangulation of data from interviews, observations, and documentation. The results of the study showed that the application of behaviorist psychology in forming learning discipline in the classroom can provide positive results if applied in the right way. Positive reinforcement has proven to be the most effective instrument in improving student discipline, while negative reinforcement and punishment need to be applied proportionally to avoid negative impacts. Teachers must have the skills to manage student behavior with an appropriate approach, pay attention to the individual character of students, and create a positive learning environment. In the long term, the proper application of behaviorist psychology will not only form student discipline, but also support the development of their personality and academic abilities.